2003
DOI: 10.1034/j.1600-0668.2003.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of endotoxin levels in carpets in New Zealand homes

Abstract: Endotoxin in house dust has been shown to be associated with asthma severity. Little is known about the influence of housing characteristics on endotoxin distribution. Using standardized methods, dust was sampled from a 1m(2) site and the whole accessible carpet area in selected Wellington, New Zealand homes (n = 77). Endotoxin was measured using a Limulus Amoebocyte Lysate assay. Relative humidity and temperature were recorded using sensors placed in carpet bases. Questionnaires were used to collect informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
63
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 28 publications
9
63
5
Order By: Relevance
“…The mean levels of endotoxins found in the USA and in Germany were slightly higher than ours [26][27][28][29][30]. Slightly lower concentrations were observed in several studies from Europe, New Zealand, and Canada [23,[31][32][33][34][35]. Our results indicate that the concentration of endotoxins present in settled dust depends significantly on the type of floor.…”
Section: Analysis Of (1→3)-β-d-glucansmentioning
confidence: 48%
“…The mean levels of endotoxins found in the USA and in Germany were slightly higher than ours [26][27][28][29][30]. Slightly lower concentrations were observed in several studies from Europe, New Zealand, and Canada [23,[31][32][33][34][35]. Our results indicate that the concentration of endotoxins present in settled dust depends significantly on the type of floor.…”
Section: Analysis Of (1→3)-β-d-glucansmentioning
confidence: 48%
“…Evidence showing that pet ownership is associated with higher house dust endotoxin levels [17][18][19]26 and the finding that children with both the TT genotype at CD14 2260 and dogs at home were least likely to have atopic dermatitis 27 suggested that the effect of pets might be mediated through endotoxin exposure. However, we did not observe a significant interaction between the CD14 2260 genotype and measures of pet exposure, nor were these interactions similar to the interaction observed for CD14 C-260T genotype and endotoxin exposure.…”
Section: Discussionmentioning
confidence: 96%
“…The presence of pets, 14,15 an increasing number of household occupants, older vacuum cleaners, a high relative humidity, and the absence of floor insulation were associated with increased endotoxin concentrations in settled household dust. 15 Endotoxin, however, represents only a part of the total microbial burden, because it occurs only in gram-negative bacteria. Peptidoglycan, in turn, is a major component of the cell wall of all species of the domain Bacteria, but not in species of the domain Archaea.…”
mentioning
confidence: 95%